A TERTIARY CARE CENTER-BASED CLINICAL INVESTIGATION OF THE FOETAL OUTCOME OF JAUNDICE IN PREGNANCY. - Kumari, Babita; Roy, Dipti (Student’s Journal of Health Research Africa, 2023)
Aim: Irregularity in the liver function runs the maternal and other pregnancy aftereffects. The main aim of the investigation is to examine the fetal outcome of high bilirubin levels in pregnancy. Methods: 61 pregnant women were examined in this study. The study was done at Nalanda Medical College for 24 months. In the beginning complete history, comprehensive clinical history, and other investigations were done. A systemic review system was used for recording the causes of liver dysfunction in pregnant women. Outcomes were studied in detail. Results: There were 61 patients in which the occurrence of jaundice was 1 and was more common in younger patients. 40% of the cases were infected with viral hepatitis, and 30% were suffering from HELLP syndrome. Conclusion: The constant problem for pregnant women is jaundice which also has unfavorable results on the neonatal outcome. Recommendation: Transfer to a tertiary care center is advocated. If the pregnant woman is at or beyond 34 weeks’ gestation or if there is any evidence of multiorgan dysfunction or severe complication, immediate induction of labor is recommended. Close monitoring of the mother should be continued after delivery.